Low-dose norepinephrine in combination with hypotensive resuscitation may prolong the golden window for uncontrolled hemorrhagic shock in rats - Zhou, Yuanqun; Li, Qinghui; Xiang, Xinming; Wu, Yue; Zhu, Yu; Peng, Xiaoyong; Liu, Liangming; Li, Tao (Frontiers in Physiology, 2022)
Hypotension resuscitation is the important principle for the treatment after the trauma. The current hypotensive resuscitation strategies cannot get ideal outcome for remote regions. With uncontrolled hemorrhagic shock (UHS) model in rats, the effects of norepinephrine (NE) on the tolerance time of hypotensive resuscitation, blood loss, vital organ functions and animal survival were observed. Before bleeding controlled, only LR infusion could effectively maintain MAP to 50-60 mmHg for 1 h, while the MAP was gradually decreased with prolonging time even with increasing infusion volume. Low-dose NE during hypotensive resuscitation prolonged the hypotensive tolerance time to 2-3 h, the effect of 0.3 μg/kg/min NE was the best. Further studies showed that 0.3 μg/kg/min NE during hypotensive resuscitation significantly lightened the damage of organ function induced by UHS via protecting mitochondrial function, while LR infusion did not. At the same time, NE administration improved Hb content, DO2 and VO2, and restored liver and kidney blood flow. The survival results showed that low-dose NE administration increased the survival rate and prolonged the survival time. Together, low-dose NE during hypotensive resuscitation was suitable for the early treatment of UHS, which can strive for golden window of emergency treatment for serious trauma patients by reducing blood loss and protecting vital organ functions.